Pseudodifferential Equation of Fluctuations of Nonstationary Gravitational Fields - Litovchenko, Vladyslav (My University, 2021)
Developing Holtzmark’s idea, the distribution of nonstationary fluctuations of local interaction of moving objects of the system with gravitational influence, which is characterized by the Riesz potential, is constructed. A pseudodifferential equation with the Riesz fractional differentiation operator is found, which corresponds to this process. *e general nature of symmetric stable random L´evy processes is determined.